Development and Validation of the Cochlear Implant Surgical Competency Assessment Instrument. Issue 4 (April 2017) - Balkany, Thomas; Lo, Kaming; Francis, Howard; Angeli, Simon; Novak, Michael; Luxford, William; Lusk, Rodney; Strader, Heather
Abstract : Objective: We present a new instrument for evaluation of cochlear implant (CI) surgical skills and review its validation process. Methods: An instrument to assess CI surgical competency incorporated results of structured surveys of comprehensiveness sent to 30 international CI experts and US trainees. One-hundred evaluations of 28 residents, fellows, and practicing CI surgeons were completed. Surgical skills were evaluated by four experienced neurotologists (two raters per subject) using two temporal bones per subject. A training session was completed by 24 subjects between the first and second procedure. Comparison of two blinded rater's scores per subject provided information on interrater reliability. Correlation of competency scores with degree of training and with improvement after a training session provided information on construct validity. Results: High levels of interrater reliability were confirmed by using the intraclass correlation coefficient. Construct validity was demonstrated by correlation of higher performance scores with increasing years of training, board certification, and fellowship training. Construct validity is also supported by improvement in scores after a CI training session as well as by acceptability surveys. Discussion: Data indicate that this instrument is an objective, accurate, and dependable procedure-specific instrument for evaluating CI surgical competency. Conclusion: The cochlear implant surgical competency assessment (CI-SCA) can be used to establish CI surgical competency, identify surgical skills that require remediation and demonstrate progress during training.